Biofabrication of biomimetic three-dimensional structures for tissue engineering - Arvins, Mariana Pinto (2023)
One of the greatest challenges associated with tissue engineering is the development of biomimetic three-dimensional structures that closely emulate the complexity and functionality of native tissues. The main objective of this work was the biofabrication of biomimetic three-dimensional structures for tissue engineering, aiming to achieve enhanced emulation of native tissue complexity and functionality, by the addition of different fractions of carbon dots. In an initial phase this work consists of the state of the art related to tissue engineering, biomaterials and scaffolds. Research was also carried out on biofabrication and its main steps and the extrusion-based bioprinting process was described. In another phase, the experimental plan was carried out, containing the materials and methods used to achieve the obtained results, such as compressive tests and 3D printing methods. Compression tests were carried out on 15 types of hydrogels composed of ColMA, CDs, and GQDs and the influence of their addition to the hydrogels was studied. It was found that the viscosity of the prepared solutions increased linearly with increasing ColMA concentration. For the same ColMA concentration, the hydrogels composed of ColMA and CDs, as the CDs concentration increased, the Young’s modulus increased. The addition of GQDs did not benefit all hydrogels, as is the case with hydrogels with a concentration of 1% ColMA, causing a decrease in Young’s modulus. 3D printing depends on several parameters such as ink viscosity, feed rate, printing pressure, needle diameter. If the feed rate is too slow, an excessive amount of material is pushed out, leading to the possibility of printing undefined structures that lack microarchitecture. On the other hand, if the feed rate is too high, there may not be enough material extruded from the nozzle, resulting in the inability to obtain any printed structures. The results obtained prove that the addition of 5% CDs can be beneficial for 3D printing, obtaining filaments with excellent uniformity, well-defined lines and angles, and good filament width.